Line 22: | Line 22: | ||

a) <math>\lambda_n^c=\lambda_n^b-\lambda_n^d</math> | a) <math>\lambda_n^c=\lambda_n^b-\lambda_n^d</math> | ||

− | b) <math>G_n = \frac{d\lambda_n^c}{dx}=-\mu (x,y_0+n\ | + | b) <math>G_n = \frac{d\lambda_n^c}{dx}=-\mu (x,y_0+n\delta d)\lambda_n^c</math> |

c) | c) |

## Revision as of 19:16, 9 July 2019

Communication, Networking, Signal and Image Processing (CS)

Question 5: Image Processing

August 2016 (Published in Jul 2019)

## Problem 1

a) $ \lambda_n^c=\lambda_n^b-\lambda_n^d $

b) $ G_n = \frac{d\lambda_n^c}{dx}=-\mu (x,y_0+n\delta d)\lambda_n^c $

c)